Serum ferritin is associated with markers of insulin resistance in Japanese men but not in women - Ngoc, Minh Pham; Akiko, Nanri; Siyan, Yi; Kayo, Kurotani; Shamima, Akter; Leng, Huat Foo; Nobuo, Nishi; Masao, Sato; Hitomi, Hayabuchi; Tetsuya, Mizoue (WB Saunders, 2013)
Objective. Several epidemiological studies have reported that high concentrations of circulating ferritin, a marker of iron stores, are related to insulin resistance (IR); however, questions remain regarding inconsistent data between Asian men and women and the inadequate consideration of potential confounding effects on the relationship between ferritin and IR. Our aim was to examine the relationship between serum ferritin concentrations and IR markers in the Japanese population. Materials/Methods. We analyzed data (n=493) from a cross-sectional survey conducted in 2009 among a Japanese working population aged 20–68 years. Fasting serum ferritin and insulin levels and fasting plasma glucose levels were determined, and the homeostatic model assessment of IR (HOMA-IR) was calculated. Multiple regression analysis was performed with adjustments for demographic and lifestyle factors, body mass index and serum C-reactive protein. Results. Fasting insulin and HOMA-IR significantly increased with increasing levels of serum ferritin after adjustment for covariates in men (P for trend=.005 and .001, respectively). Compared with men in the lowest tertile of serum ferritin, those in the highest tertile had a 24% higher HOMA-IR score. Additional data suggested a positive association between iron intake and HOMA-IR (P for trend=.07) in men. Neither serum ferritin nor iron intake was related to IR markers in women, even in postmenopausalwomen. Conclusions. Serum ferritin concentrations were positively associated with fasting insulin and HOMA-IR in men but not in women, suggesting an important role of iron storage in the pathogenesis of IR in Japanese men.